The Dynamics of Quarter Life Crisis and Coping Strategies for Final Year Undergraduate Students: The Dynamics of Quarter Life Crisis and Coping Strategies for Final Year Undergraduate Students - Ferani Amira Salsabila; Fransiska Harsyanthi; Ira Mustika; Wulan Sari Putri Hidayat; Yulina Eva Riany (Journal of Family Sciences, 2023)
Quarter-life crisis is a crisis that occurs in individuals aged 20 years and over. In this phase it becomes a difficult phase because of a significant change, previously the individual focused on spending school years but after that he was forced to take responsibility for himself. The purpose of this study is to see the dynamics of the quarter life crisis and coping strategies carried out by individuals who are carrying out lectures at IPB University. The purpose of this study is to look at the dynamics of quarter-life crises and coping strategies by individuals who are currently running lectures at the final year undergraduate. The respondents in the study were 11 final year undergraduate students who were carrying out lectures at the final level. Data were collected using semi-structured interviews and focus group discussions (FGD). The results showed that each individual experienced a different quarter-life crisis, with the most of problems faced are anxiety about the future. Each individual has a different coping strategy in dealing with the crisis they are experienced. The differences comes because of differences in responding problem, parenting style and personality.